Computer-assisted Control of a Waiting List - Rourke, T. A.; McFadden, E.; Rogers, A. C. N. (Methods of Information in Medicine, 1977)
The main objective in the use of computer-based systems which dynamically order hospital waiting lists is to produce a more systematic and clinically acceptable pattern of selection from the waiting list than that resulting from traditional manual systems. This has been achieved previously through the evaluation of fairly complex mathematical formulae which require detailed analysis to modify their behaviour pattern, and thus separate the clinician from direct control of the system.This paper describes a waiting list management system which uses a conceptually simple ordering process based on waiting time limits set by the clinician for each planned clinical procedure relevant to the specialty. The clinician receives periodic analyses of the current performance of the process and can easily control the behaviour pattern by changing the limits for any procedure. The system also keeps account of allocated bed and theatre resources.Use of this waiting list management system in a Urology Department has resulted in a significant shift in the composition of the waiting list and in a more equitable pattern of selection from the waiting list;. In addition, the time spent by the clinician in managing the waiting list has been considerably reduced.
Keywords: Waiting List Management; Waiting List Ordering; Admissions Scheduling; Resource Allocation